Quantitative assessment of environmental impacts on life cycle of highways. - Kwangho Park
Several representative environmental loads emitted from the life cycle of highways, which form one of the major infrastructure sectors, were estimated. The life cycle of highways was divided into four stages-manufacturing of construction materials, construction, maintenance/repair, and the demolition/recycling stage. Energy consumption in each life cycle stage was quantified, and environmental load was estimated by applying the environmental emissions factor per each energy source. As a result, it is estimated that the most energy was consumed in the manufacturing stage of construction materials, with consumption of 1,525.8 tons of oil equivalent per functional unit (1 km and four lanes of highways). Energy consumption in the maintenance and repair stage was also relatively high among the life cycle stages; the next highest consumption was for the construction and demolition stage. Through the whole life cycle of 20 years, 2,676.8 TOE of energy per functional unit was consumed, and this corresponds to SO2, NOx, and CO2 emissions of 62.1 tons, 17.1 tons, and 2,438.5 T-C, respectively.
Keywords: Environmental impacts; Highways